Parental care in the Small Tree Finch Camarhynchus parvulus in relation to parasitism and environmental factors. (27th May 2020) - Heyer, Eileen; Cimadom, Arno; Wappl, Christian; Tebbich, Sabine
Abstract : The parental food compensation hypothesis suggests that parents may compensate for the negative effects of parasites on chicks by increased food provisioning. However, this ability differs widely among host species and may also depend on ecological factors such as adverse weather conditions and habitat quality. Although weed management can improve habitat quality, management measures can bring about a temporary decrease in food availability and thus may reduce parents' ability to provide their nestlings with enough energy. In our study we investigated the interaction of parasitism and weed management, and the influence of climate on feeding rates in a Darwin's tree finch species, which is negatively impacted by two invasive species. The larvae of the invasive parasitic fly Philornis downsi ingest the blood and body tissues of tree finch nestlings, and the invasive Blackberry Rubus niveus affects one of the main habitats of Darwin's tree finches. We compared parental food provisioning of the Small Tree Finch Camarhynchus parvulus in parasitized and parasite‐free nests in three different areas, which differed in invasive weed management (no management, short‐term and long‐term management). In a parasite reduction experiment, we investigated whether the Small Tree Finch increases food provisioning rates to nestlings when parasitized and whether this ability depends on weed management conditions and precipitation. Our results provide no evidence that Small Tree Finches can compensate with additional food provisioning when parasitized with P. downsi . However, we found an increase in male effort in the short‐term management area, which might indicate that males compensate for lower food quality with increased provisioning effort. Furthermore, parental food provisioning was lower during rainfall, which provides an explanation for the negative influence of rain on breeding success found in earlier studies. Like other Darwin's finches, the Small Tree Finch seems to lack the ability to compensate for the negative effects of P. downsi parasitism, which is one explanation for why this invasive parasite has such a devastating effect on this host species.